Prompt photocatalytic purification of dye wastewater using zinc doped nickel oxide nanostructures and Artima salina model for acute toxicity screening - M.B. JessieRaj; M. Pavithra (Next Nanotechnology)
Industrial organic contaminates in water bodies are toxic not only to aquatic plants and animals but also to the entire ecosystem. The present study focuses on eradicating these industrial pollutants using zinc ions doped nickel oxide nano photocatalysts. Ultrasonication-aided co-precipitation method was used to synthesize Zn doped NiO nanoparticles which were further analyzed for their structural, optical, morphological, elemental, and photocatalytic abilities. Bragg diffraction patterns of synthesized samples revealed that zinc ions were successfully loaded in the NiO lattice as cubic nano-crystallites with Fm3m, space-group. FTIR study supported the formation of Zn –Ni linkages and Ni-O stretching vibrations. Tauc plot found that optical band gap energy decreases from 3.2 to 2.7 eV. PL study revealed the charge recombination process delayed by an intermediate band to enhance photocatalytic activity. The formation and reduction of clear rectangular rod structures by increasing zinc dopant materials and the composition of Ni, Zn, and O elements were explored in SEM-EDX images. XPS, TEM and SAED patterns corresponded quite well with the XRD results. Pseudo-first-order kinetics of photocatalytic degradation analysis predicted that Zn doped NiO nanostructures show their suitableness for preventing Rhodamine B and 4-Nitrophenol contaminates (up to 95 % and 80 %) in aquatic media under direct sunlight. Further, detox and practical usage of Zn doped NiO were confirmed by the Artemia salina organism’s considerable lifespan in the treated water using a toxicity evaluation model. Based on these observations, it is expected to facilitate an expedited remedy of toxicity screening for regulatory purposes.